Implementasi Light Dependent Resistor (LDR) Pada Simulasi Permainan Gobak Sodor - Rizky Eka Adinagoro; Putra, Reza Aditya Angga; Rahadian Bintang Pamungkas; Satya Yoma Patria Risky; Rudi Susanto (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
Gobak sodor is a traditional Indonesian game. This article is compiled to relate to the application of detection tools in the simulation of the gobak sodor game. The goal is to produce a prototype of a tool that can help facilitate the detection process in the movement of the gobak sodor game. The method used is the RAD (Rapid Application Development) method which has stages, namely requirement planning, design workshop and implementation, data collection techniques, namely literature studies, and documentation. As a result of the implementation of this tool, it will be able to work automatically when there is a player who crosses the line will block the light reaching the LDR. The findings of this device, the existence of an alarm and lights turn on when there are players who cross the barrier line. This is because a change in resistance in the LDR triggers an alarm system or indicator light to detect movement. If the player's body hits the LDR sensor, then the device will sound.